A Cultural Project of Control: The Foundation of Calcutta Madrassa and the Benares Sanskrit College in India - Mahmut İzgi (Skad)
In the beginning of the seventieth century, British merchants made serious effort for gaining a share form the lucrative commercial activities in India with the help of the British East Indian Company. In the earliest times, the trade was the main activity of the Company’s servants but due to the political condition of the subcontinent such as the breakdown of the Mughal authority and political struggle of the local powers, the Company began to appear as a political figure. Subsequently, by the middle of the eighteenth century, the Company’s servant played considerable role to protect the British presence in Indian subcontinent. Apart from the political and military measures, the first general-governor of Warren Hastings imposed the Orientalist education policy for producing elite corps to keep India as part of the Company. In this sense this paper investigate the Hastings policy in the light of the establishment of two important education centers.